Effect of inoculations with single and multiple juveniles on release of progeny of Meloidogyne graminicola from susceptible rice - Reversat, Georges; Fernandez, Luzviminda (Brill, 2004)
Seedlings of susceptible rice were inoculated with single or with 86 second-stage juveniles (J2) of Meloidogyne graminicola. After inoculation in a sandy substrate, rice seedlings were grown hydroponically to recover progeny. Following inoculation with a single juvenile (SJI), 71-73% of seedlings released J2 progeny at 84 days after inoculation (DAI). This confirmed the ability of this species to reproduce by parthenogenesis. After SJI, the proportion of inoculated seedlings releasing J2 increased steadily from 21-63 DAI. On the contrary, after inoculation with 86 J2, release of progeny was high for all seedlings as early as 28 DAI. Thus progeny formed after SJI remained captive in galls for a longer time. In the same sandy substrate, J2 were able to invade rice roots and develop in flooded conditions as well as in non-flooded conditions.